BENDE WUTA (BENTENG TANAH) DALAM KONTEKS SEJARAH BUDAYA MEKONGGA SULAWESI TENGGARA - nfn Hasanuddin (WalennaE, 2010)
This research was conducted in Wundulako, Kolaka, Southeast Sulawesi, which express the geographic location of the fort the ground, and it contains a number of artifacts through survei and excavation methods. Archaeological data in said Collaborate with tradition and geological data. Citadel Land (Bende Wuta) was established by Latoranga the XVII century (around 1676). Survei data to produce findings of a metal currency (coins), fragments of pottery and ceramics. Excavation data showed the existence of the artificial soil structure and modification of forms of material available in the vicinity. From the comparative aspect that shows the shape of the blockhouse and fortified the settlement as well as the king and his family. Besides, the position of land fort called Wuta Bende is 471 m from the river showed Lamekongga maintaining a strategic position in the kingdom's sovereignity Mekongga.Penelitian ini dilakukan di Wundulako, Kolaka, Sulawesi Tenggara, yang mengungkapkan lokasi geografis benteng alam, dan berisi sejumlah artefak melalui metode survei dan ekskavasi. Data arkeologi di katakan Berkolaborasi dengan data tradisi dan geologi. Citadel Land (Bende Wuta) didirikan oleh Latoranga pada abad XVII (sekitar 1676). Survei data untuk menghasilkan temuan mata uang logam (koin), pecahan tembikar dan keramik. Data penggalian menunjukkan adanya struktur tanah buatan dan modifikasi bentuk bahan yang tersedia di sekitarnya. Dari aspek komparatif yang menunjukkan bentuk benteng yang melindungi raja dan keluarganya. Selain itu, posisi benteng tanah yang disebut Wuta Bende berjarak 471 m dari sungai menunjukkan Lamekongga mempertahankan posisi strategis dalam kedaulatan kerajaan Mekongga.